Penyelesaian Sengeketa Ekonomi Syariah dan Poltik Hukum Yang Mempengaruhinya - Albi Haris Jen, Muhammad; Zaki Ibrahim, Hilmi (UIN Sunan Gunung Djati Bandung, 2025)
The development and growth of Islamic economic practices in Indonesia has moved very significantly. This is due to the increased public awareness of the true practice of religion in the economic field and the political will of the government to support the development of the Islamic economy in Indonesia. a very interesting thing, if there is a dispute over sharia economic contracts, then the legal politics will affect the authorized institution in resolving sharia economic disputes in Indonesia. The purpose of this study is to understand the legal politics of the authority to resolve sharia economic disputes in Indonesia. The method used in this study is a descriptive method with a normative juridical approach, the use of data is primary and secondary data taken by way of literature study. The results of the study found that legal politics in the authority of sharia economic dispute resolution consists of three aspects, namely regulation, institutional aspects, and human resource aspects.